Analisis Faktor yang Berhubungan dengan Kejadian Seksio Sesarea Berulang di Rumah Sakit Umum Daerah Kota Kendari Periode 2023-2024 - Wa Ode Nurhiqmah Basri, Wa Ode Nurhiqmah Basri; Juminten Saimin; Livy Leonard Lieswan (Faculty of Medicine, Universitas Mataram, 2025)
Cesarean section (CS) deliveries have increased globally to 30% and reached 25.9% in Indonesia. Kendari City Regional Hospital shows a higher rate of 37.5%, exceeding the WHO recommendation of 30%. This increase is associated with rising risks of morbidity and mortality in both mothers and babies. One of the main contributors is repeat cesarean sections, which account for more than one-third of all cesarean deliveries globally. Repeat cesarean sections carry higher risks of intraoperative complications and uterine rupture, making this group a high-risk category that requires special attention in efforts to reduce maternal and perinatal morbidity and mortality rates. Method. This was an analytical observational study using a cross-sectional design based on medical record data. The study population included all mothers who delivered via cesarean section at the Regional General Hospital of Kendari during 2023–2024. A total of 245 samples were selected using purposive sampling. Data were analyzed using the chi-square test, with a significance level set at > 0.05. Results. The study found 148 cases (60.4%) were repeat cesarean sections and 97 cases (39.6%) were primary cesarean sections. The analysis showed significant associations between maternal age (p=0.000) and PROM (p=0.000) with repeat CS. There was no significant association between cervical dilatation (p=0.172) and repeat CS. Conclusion. This study demonstrates significant associations between maternal age and premature rupture of membranes with the incidence of repeat cesarean section at Kendari General Hospital during 2023–2024.